COVID-19 outbreak and cancer radiotherapy disruption in Italy: Survey endorsed by the Italian Association of Radiotherapy and Clinical Oncology (AIRO). (August 2020) - Jereczek-Fossa, Barbara Alicja; Pepa, Matteo; Marvaso, Giulia; Bruni, Alessio; Buglione di Monale e Bastia, Michela; Catalano, Gianpiero; Filippi, Andrea Riccardo; Franco, Pierfrancesco; Gambacorta, Maria Antonietta; Genovesi, Domenico; Iatì, Giuseppe; Magli, Alessandro; et al.
Abstract: Italy experienced one of the world's deadliest COVID-19 outbreaks and healthcare systems had to instantly reorganise activity. The Italian Radiation Oncology Departments adapted numerous solutions to minimize the disruptions. Information technologies, treatment prioritization and implementation of hypofractionation and protection procedures allowed balancing between cancer patient care and patient/healthcare workers safety.